AUDIT OF OXYGEN PRESCRIBING IN A CHILDREN'S HOSPITAL. Issue 9 (17th August 2016) - Wheeler, Lucy; James, Janet; Byrne, Sarah; Forton, Julian
Abstract : Aim: To audit oxygen prescribing in a children's hospital following the introduction of a new paediatric medication chart, which incorporates an oxygen prescription section. Method: In June 2015 a 1-day snapshot audit was carried out across all wards in the children's hospital. All patients receiving oxygen on that day were included: ▸ The audit was repeated in July 2015. ▸ The standards for the audit were set at 100% in accordance with our local guidelines.1 ▸ All patients receiving oxygen should have a prescription. Of these: ▸ All patients should have target saturations identified. ▸ All patients should have an administration device identified. ▸ All patients should have a nurse signature on the chart within the last 12 hrs. Results: In June, 13 patients were receiving oxygen on the audit day. 0/14 had a prescription. In July, 18 patients were receiving oxygen on the audit day. (14 critical care, 4 medicine). 4/18 had an oxygen prescription (22%). These were all medical patients. Of these, 4 patients had a target saturation identified (100%), 1 had a device prescribed (25%), and 4 had a nurse signature within the last 12 hrs (100%). Conclusion: The initial audit showed no compliance with either local or national guidance for oxygen prescribing.1 2 The re-audit showed improved prescribing on the medical wards but not within critical care. The new paediatric medication chart was launched early in 2015, along with a training package for doctors, nurses and pharmacists. This was in response to the National Patient Safety Agency (NPSA) rapid response report on oxygen safety in hospitals.3 There was a gap between the training and the new charts being available which may have led to the poor results in the first audit. Increased awareness of the charts and the initial audit results probably helped improve prescribing in the re-audit. For medical patients, prescribing and monitoring was good, although device was infrequently prescribed. Critical care have not engaged with the new chart and oxygen prescription process. Although the British Thoracic Society guidelines indicate that oxygen for adult patients must be prescribed, these do not currently cover critical care or children under 16 years.2 There are guidelines for children in development which are likely to advocate the same. This could be another reason why there is no prescribing in critical care. Patient numbers were small in this snapshot audit which could limit its validity. Future work will include re-audit in our hospital and audit across the whole region where the new charts have been introduced.